ANALISIS KELAYAKAN USAHA BUDIDAYA RUMPUT LAUT (Eucheuma cottonii) (STUDI KASUS DI DESA KARIMUN JAWA KECAMATAN KARIMUN JAWA KABUPATEN JEPARA) - Nuryanto Nuryanto; Lutfi Aris Sasongko; Eka Dewi Nurjayanti (MEDIAGRO, 2016)
Seaweed is one of the world trade leading comodity. Indonesia is a provider country of seaweed as an industrial raw material. The purposes of  this research are to know revenue and income of the seaweed cultivation in Karimun Jawa Village Karimun Jawa District Jepara Regency and feasibility of seaweed cultivation  in term of R/C and BEP. This research used descriptive method, while the respondents chosen purposively (20 respondents). Data will be analyzed to find revenue level, income level and feasibility analysis in term of R/C and BEP. Activity in the seaweed cultivation consist of site selection, seed preparation, plant distance setting, maintenance and harvesting. The research results showed that seaweed cultivation requires  a fixed cost  Rp787.454,00/plant season/hectare consist of depreciation cost. While  the variable cost  is  Rp2.817.200,00/plant season/hectare consist of seed cost and labor cost. Seaweed cultivation business revenue is Rp5.191.000,00/plant season/ hectare and obtained an income  Rp1.586.546,00/plant season/ hectare. Feasiblity of seaweed cultivation in terms of R/C was 1,44, which means the business is feasible. Then, in term of BEP(q) is 1.366 kg and BEP (Rp) is Rp1.719.331. To increase the farmers income, the harvest result of seaweed can be processed into flour seaweed and processed products such as dodol, crispy onions, etc. Keyword : seaweed cultivation,  revenue,  income,  feasibility analysis